Diatomic catalyst screening method, iron / vanadium diatomic catalyst, and preparation method and application of iron / vanadium diatomic catalyst

The diatomic catalyst screening method calculated by density functional theory was screened and prepared iron/vanadium diatomic catalysts, which solved the problem of insufficient catalyst performance in the prior art, achieved efficient removal of organic micropollutants in water, and showed stable and efficient activity within a wide pH range.

CN119869576APending Publication Date: 2025-04-25MUNICIPAL ENVIRONMENTAL PROTECTION ENG CO LTD OF CREC SHANGHAI GRP +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510067772.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the advanced oxidation process based on peroxymonosulfate, the performance of the catalyst is insufficient, resulting in low removal efficiency of organic micropollutants in water, and lack of effective screening methods to quickly and accurately screen out highly active diatomic catalysts.

Method used

The diatomic catalyst screening method calculated by density functional theory is used to screen iron/vanadium diatomic catalysts by adsorption energy and electron transfer amount as main descriptors, and the catalyst is prepared by a specific preparation method.

Benefits of technology

It has achieved efficient removal of organic pollutants in the water BPA and photovoltaic wastewater effluent. The catalyst exhibits stable and efficient activity within a wide pH range, reaching 100% removal rate within 6 minutes, and the reaction rate constant can reach 0.98min-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869576A_ABST
    Figure CN119869576A_ABST
Patent Text Reader

Abstract

The invention discloses a double-atom catalyst screening method, an iron / vanadium double-atom catalyst, and a preparation method and application of the iron / vanadium double-atom catalyst. The screening method comprises the following steps: S1, taking adsorption energy and electron transfer amount as descriptors for evaluating the PMS adsorption and activation capability of a catalyst, carrying out first-step screening on M-MXene loaded with monatomic metals according to a sequence of adsorption energy from high to low, obtaining M-MXene which is ranked as top n, and screening to obtain n metals M; step S2, pairing n kinds of metals M in pairs to obtain a diatomic pairing carrier M1-M2-MXene group; and S3, carrying out differential charge calculation, and screening out the M1-M2-MXene with the highest electron transfer amount as the diatomic catalyst. The iron / vanadium diatomic catalyst with the MXene as the substrate prepared by screening can activate PMS, has high and stable removal rate and removal efficiency for bisphenol A, can completely remove 20 mg / L of BPA within 6 min, and has a maximum reaction rate constant of 0.98 min <-1 >. The method is simple in screening step, easy to control, high in practicability and suitable for efficient screening of the diatomic catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of water purification, and relates to the application of catalysts in advanced oxidation processes based on peroxymonosulfate and related mechanism research, and specifically relates to a diatomic catalyst screening method, an iron / vanadium diatomic catalyst, and a preparation method and use thereof. Background Art

[0002] As the global shortage of clean water resources becomes increasingly serious, the development of urban water purification technology has become critical. Peroxymonosulfate-based advanced oxidation processes (PMS-AOPs) have shown great practical potential in the field of water purification because they can produce a large number of reactive oxygen species by activating peroxymonosulfate (PMS), thereby quickly removing organic micropollutants in water. In PMS-AOPs, the performance of the catalyst is crucial for activating PMS, which directly affects the generation efficiency of reactive oxygen species and the removal effect of organic micropollutants.

[0003] Although single-atom catalysts (SACs) based on transition metals (iron, copper, cobalt, manganese, etc.) have attracted widespread attention in Fenton-like reactions, their dispersed metal sites, easily adjustable electronic structures, and identifiable coordination provide a certain basis for studying structure-activity relationships, but they have obvious shortcomings in the PMS activation process. For example, PMS activation includes two key steps: adsorption and activation. The isolated active sites in SACs are difficult to meet the scaling relationship of multi-step reactions, which to some extent limits their activation efficiency for PMS and their ability to remove organic micropollutants.

[0004] Compared with SACs, diatomic catalysts (DACs) show higher reactivity in Fenton-like reactions, and the synergistic effect between diatomic sites also provides more possibilities for catalytic mechanisms, but they face more complex electronic structure problems. At present, the primary challenge in the study of DACs is how to accurately design cooperative diatomic pairs to achieve higher reactivity. At the same time, there is a lack of suitable descriptors to effectively correlate experimental and theoretical results, which makes it difficult to explore its catalytic mechanism and evaluate its activity, and it is difficult to quickly and accurately screen out highly active diatomic pairs for practical water purification applications. Summary of the invention

[0005] The purpose of the present invention is to improve the efficiency and sustainability of urban water purification, solve the technical problem of removing organic micropollutants in water, and provide a diatomic catalyst screening method based on density functional theory calculation. Based on this method, an iron / vanadium diatomic catalyst is screened and prepared, and the catalyst is used to treat BPA in water and organic pollutants in photovoltaic wastewater effluent. The catalyst of the present invention has high removal efficiency for BPA and organic pollutants in photovoltaic wastewater effluent, and has good practicality and stability.

[0006] In order to achieve the above object, the present invention provides a method for screening diatomic catalysts, comprising the following steps:

[0007] Step S1, using adsorption energy and electron transfer amount as descriptors for evaluating the ability of the catalyst to adsorb and activate PMS, the M-MXene loaded with single-atom metals is sorted from high to low according to the adsorption energy, and the first n M-MXenes are obtained, thereby screening n types of metals M;

[0008] Step S2, pairing the n metals M in pairs to obtain a diatomic pairing carrier M1-M2-MXene group;

[0009] Step S3, performing differential charge calculation on the M1-M2-MXene group, and selecting the M1-M2-MXene with the highest electron transfer amount as a diatomic catalyst.

[0010] Optionally, the single-atom metal includes at least four of iron, copper, cobalt, manganese, vanadium, nickel and zinc.

[0011] Optionally, n is 3 or 4, and the M1-M2-MXene is an iron / vanadium diatomic catalyst.

[0012] The present invention also provides a method for preparing an iron / vanadium diatomic catalyst, comprising:

[0013] Step 1: Ti3C2T x MXene is dispersed in ultrapure water to obtain mixed solution I;

[0014] Step 2, adding FeCl3·6H2O and NH4VO3 into the mixed solution I and stirring evenly to obtain a mixed solution II;

[0015] Step 3, filtering the mixed solution II and drying it to obtain solid powder I;

[0016] Step 4, placing the solid powder I in a tube furnace and calcining at high temperature under a protective atmosphere to obtain a solid powder II;

[0017] Step 5, washing the solid powder II with acid and water for several times until the pH of the solution is >6.5, filtering, and drying to obtain iron / vanadium diatomic catalyst powder.

[0018] Optionally, the molar ratio of FeCl3·6H2O to NH4VO3 is 1:(1-2).

[0019] Optionally, in step 4, the high temperature calcination temperature is 500°C to 900°C, and the heating rate is 3-10°C·min -1 .

[0020] The present invention also provides an iron / vanadium diatomic catalyst, which is formed by loading iron and vanadium in Ti3C2Tx MXene, wherein the molar ratio of iron to vanadium is 1:(1-2), and the molar ratio of Fe to Ti3C2Tx MXene is (0.25-1:1).

[0021] The present invention also provides a use of the above-mentioned iron / vanadium diatomic catalyst for treating bisphenol A in water or for treating photovoltaic wastewater.

[0022] Optionally, the method for treating bisphenol A in water comprises: adding the iron / vanadium diatomic catalyst to the water to be treated and mixing evenly, then adding potassium persulfate, adjusting the pH of the water to 3-11 and the water temperature to 293-313K; wherein the dosage of the iron / vanadium diatomic catalyst is 0.5-2.0 g / L.

[0023] Optionally, the method for treating photovoltaic wastewater comprises: fixing the iron / vanadium diatomic catalyst in a filtration treatment device, allowing photovoltaic wastewater mixed with potassium monopersulfate to pass through, and discharging treated water.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The screening method based on density functional theory calculation of the present invention uses adsorption energy and electron transfer amount as the main descriptors to predict material properties, and screens out iron / aluminum diatomic catalyst materials based on this. The screening method is simple, efficient and low in cost. The iron / aluminum diatomic catalyst material has high and stable efficiency in activating PMS and removing pollutants BPA in the pH range of 3-11 in water, with a removal rate of 100% in 6 minutes and a reaction rate constant of 0.98min -1 .

[0026] Furthermore, the composite material of the present invention has good stability, and the Fe-V-MXene / PVDF / PMS system developed based on the catalyst still has a removal rate of more than 70% after 8 hours of continuous flow treatment of photovoltaic wastewater effluent. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The adsorption energy calculation diagram and electron transfer calculation diagram of various M-MXenes implemented for calculation; among them, (a) represents the adsorption energy diagram of PMS loaded with different metal atoms on the MXene carrier, and (b) represents the electron transfer diagram between various metals and PMS.

[0028] Figure 2 Charge density difference plot for the calculations performed.

[0029] Figure 3The atomic local structure and chemical state of Fe-V-MXene. (a) represents the normalized XANES spectrum of Fe element; (b) represents the Fourier transform k of Fe-V-MXene and reference samples (FeO, Fe2O3, Fe3O4, Fe foil). 3 Weighted EXAFS data; (c) is the fitting data of the Fe element in Fe-V-MXene in (b); (d) represents the normalized XANES spectrum of the V element in R space (schematic diagram of the position of V in space); (e) represents the Fourier transform k of Fe-V-MXene and reference samples (VO2, V2O3, V2O5, V foil (vanadium foil)) 3 Weighted EXAFS data, (f) is the fitting data of the V element in Fe-V-MXene in (e), (g)-(j) represent the k of Fe-V-MXene and reference samples 3 Wavelet transform of weighted EXAFS data.

[0030] Figure 4 This is the XRD pattern of Fe-V-MXene.

[0031] Figure 5 FT-IR graph of Fe-V-MXene.

[0032] Figure 6 This is a diagram showing the removal efficiency of BPA by activating PMS under different pH conditions of Examples 6 to 12;

[0033] Figure 7 This is a diagram showing the removal efficiency of BPA by activating PMS with Fe-V-MXene under different catalyst dosage conditions of Examples 13 to 15;

[0034] Figure 8 Experimental flow chart of Fe-V-MXene / PVDF system.

[0035] Fig. 9 This is the operating efficiency diagram of the Fe-V-MXene / PVDF system for photovoltaic wastewater effluent. DETAILED DESCRIPTION

[0036] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] In the description of the present invention, it should be noted that the terms "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0038] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0039] The Fenton-like reaction is an extension and improvement of the traditional Fenton reaction. The traditional Fenton reaction refers to the reaction of ferrous ions (Fe 2+ ) reacts with hydrogen peroxide (H2O2) to produce hydroxyl radicals (·OH) and other active oxidizing substances. The Fenton-like reaction is a similar oxidation process that uses different catalysts or triggering methods under a wider range of conditions to produce free radicals with strong oxidizing ability, thereby degrading various organic pollutants. The Fenton-like reaction is an advanced oxidation technology that has a wide range of applications in fields such as environmental protection and medicine.

[0040] The core idea of ​​density functional theory is to express the properties of the system as a function of the electron density. In quantum mechanics, solving the Schrödinger equation for a multi-electron system is very complicated, while density functional theory greatly simplifies the calculation by expressing the energy of the system as a functional of the electron density. Specifically, the total energy of the system can be divided into several parts: kinetic energy, interaction energy between electrons, external potential field (interaction between nuclei and electrons), etc. Through the variational method, the expressions of the ground state electron density and energy of the system can be obtained. In density functional theory, the exchange-correlation functional is introduced to describe the complex interactions between electrons. The application method of density functional theory includes the following steps: 1) Select a suitable exchange-correlation functional according to the nature and accuracy requirements of the research problem; 2) Construct a system model: First, determine the geometric structure and electronic structure of the research system. For Fenton-like reactions, a model of the catalyst can be constructed, including its crystal structure, surface structure, etc. At the same time, it is also necessary to consider the adsorption of reactants (such as H2O2, organic pollutants, etc.) on the catalyst surface. Then, quantum chemistry software such as VASP and Gaussian are used to model and calculate the system. In the modeling process, it is necessary to reasonably set the calculation parameters, such as basis set, cutoff energy, etc., to ensure the accuracy and efficiency of the calculation. 3) Perform calculations and analysis: Use density functional theory to calculate the energy, electron density, charge distribution and other properties of the system. By analyzing these properties, the mechanism of Fenton-like reactions can be revealed, such as the electron transfer process on the catalyst surface, the determination of active sites, etc. For Fenton-like reactions, descriptors such as OO bond length, adsorption energy, charge transfer, d-band center, etc. can be calculated. These descriptors can help us understand the activity and selectivity of the catalyst, as well as the kinetics and thermodynamics of the reaction.

[0041] In the field of Fenton-like reactions, although density functional theory calculations have been widely used in mechanism exploration, and many descriptors (such as OO bond length, adsorption energy, charge transfer, d-band center, etc.) are often used to reveal catalytic mechanisms, due to the complex electronic structure and reaction mechanism of DACs, the existing descriptors are still unable to fully correlate with experimental results in this field. In addition, these descriptors are often only used in research to describe the mechanism, but rarely in catalyst design. Therefore, in the field of Fenton-like reactions, there is still a lack of methods and practices for predicting the activity of diatomic catalysts through density functional theory calculations, so as to accurately evaluate the activity of diatomic sites, which also hinders the development of efficient catalysts.

[0042] To this end, the present invention provides a specific process for screening Fe-V-MXene materials, comprising the following steps:

[0043] Step S1, taking the adsorption energy and the amount of electron transfer between the carrier and the persulfate molecule as the main descriptors for evaluating the ability of the catalyst to adsorb and activate PMS, the M-MXene loaded with single-atom metals is sorted from high to low according to the adsorption energy, and the first step of screening is performed to obtain the top n M-MXenes, and screen out n metals M. In some embodiments, the single-atom metals include at least 4 of iron, copper, cobalt, manganese, vanadium, nickel, and zinc.

[0044] Step S2, pairing the n metals M in pairs to obtain a diatomic pairing carrier M1-M2-MXene group. In this example, V, Mn, and Fe, which are ranked in the top three in terms of adsorption energy, are paired in pairs to obtain dimetallic atomic groups including V-Mn, V-Fe, and Mn-Fe.

[0045] Step S3, performing differential charge calculation on the M1-M2-MXene group, and selecting the M1-M2-MXene with the highest electron transfer amount as a diatomic catalyst. Specifically, the M1-M2-MXene with higher adsorption energy or electron transfer amount between the carrier and the persulfate molecule is regarded as a potential high-efficiency catalyst, and the high-efficiency electron transfer between the diatoms is further analyzed by charge density difference and differential charge (i.e., charge after adsorption of PMS minus charge before adsorption), and a diatomic catalyst with high activity, i.e., an iron / vanadium diatomic catalyst, is selected.

[0046] Figure 1 (a) shows the adsorption energy diagram of PMS with different metal atoms loaded on MXene carriers. Figure 1 (b) shows the density of states diagram of the carrier and PMS.

[0047] Depend on Figure 1 (a) shows that among different M-MXenes, the adsorption energies of V, Mn, Fe, Co, Cu, Ni, and Zn loaded MXene with PMS are -4.01, -3.91, -3.62, -3.06, -2.61, -2.83, and -3.52 eV, respectively. Subsequently, three atoms (V, Mn, and Fe) were selected for further diatomic loading calculations because they have higher adsorption energies. Ultimately, Fe-V-MXene exhibited the highest adsorption energy (-5.33 eV), indicating that this structure has the highest PMS adsorption energy. The activation ability of the catalyst was further evaluated by charge transfer using Bader charge analysis, as shown in Figure 5. Figure 1 As shown in (b). Among them, Fe-V-MXene exhibits the highest charge transfer value of 2.60|e|, which is also significantly higher than Fe-MXene and V-MXene, thus screening out the Fe-V diatomic catalyst.

[0048] The charge density difference further reveals the charge transfer between different metal sites. Figure 2 The charge density difference (ie, differential charge density) diagram of V-MXene-PMS, Fe-MXene-PMS, and Fe-MXene-PMS is shown. Figure 2 As shown in Figure 2, stronger chemical interactions of charge transfer were observed around the Fe-V diatoms and PMS molecules in Fe-V-MXene-PMS. In addition, the charge density near the iron atom (Fe-MXene-PMS) was significantly enhanced, and V-MXene-PMS also showed similar results ( Figure 2 ). However, the formation of the Fe-V diatomic site significantly changes the charge density difference. The charge density near the Fe-V diatomic region shows a two-level differentiation, forming an electron accumulation region near the Fe atom and an electron depletion region near the V atom. This shows that with the redistribution of electrons, the electrons of the V atom are further transferred to the Fe atom, which is conducive to the formation of coordination between the Fe-V diatoms and promotes the catalytic reaction. In this case, the iron / vanadium (Fe-V) diatomic catalyst was screened.

[0049] The present invention provides an iron / vanadium diatomic catalyst (Fe-V-MXene) having the following characteristics: Figure 3 The atomic local structure and chemical state shown. Among them, (a) represents the normalized XANES spectrum of Fe element; (b) represents the Fourier transform k of Fe-V-MXene and reference samples (FeO, Fe2O3, Fe3O4, Fe foil (iron foil)) 3 Weighted EXAFS data; (c) is the fitting data of the Fe element in Fe-V-MXene in (b); (d) represents the normalized XANES spectrum of the V element in R space (schematic diagram of the position of V in space); (e) represents the Fourier transform k of Fe-V-MXene and reference samples (VO2, V2O3, V2O5, V foil (vanadium foil)) 3 Weighted EXAFS data, (f) is the fitting data of the V element in Fe-V-MXene in (e), (g)-(j) represent the k of Fe-V-MXene and reference samples 3 Wavelet transform of the weighted EXAFS data shows the fitted k-space curve, which shows the atomic pairing of Fe-V-MXene.

[0050] like Figure 3 As shown in (a), the K-edge absorption threshold of Fe in Fe-V-MXene is between FeO and Fe2O3, indicating that the valence state of Fe in Fe-V-MXene is between +2 and +3. The Fourier transform (FT) k 3 Weighted EXAFS image, see Figure 3(c), two peaks appear at 1.7 and 2.6, corresponding to Fe-O and Fe-V, respectively. In addition, the VK edge absorption threshold of Fe-V-MXene is closer to the standard reference V2O3 ( Figure 3 d), indicating that V in Fe-V-Mxene is in an oxidized state. Figure 3 (g)-(j) show k 3 Wavelet transform of weighted EXAFS data shows that the Fe-V sites of Fe-V-MXene are well paired and well distributed. These results confirm that the Fe and V atoms on the Fe-V-MXene surface are well dispersed.

[0051] Figure 4 The XRD patterns of Fe-MXene, V-MXene, and Fe-V-MXene are shown. In the XRD pattern, Fe-V-MXene shows a peak surface similar to that of V-MXene, indicating that the overall structure of Fe-V-MXene is more similar to that of V-MXene.

[0052] Figure 5 The FT-IR graph is shown, and characteristic peaks of oxygen-containing functional groups -OH, C=O and Ti-O are detected in the FT-IR spectrum. This indicates that oxygen-containing functional groups are widely present on the surface of MXene, which is beneficial to the coordination and fixation of Fe and V atoms.

[0053] The present invention also provides a method for preparing the iron / vanadium diatomic catalyst material, comprising the following steps:

[0054] Step 1, dispersing 400 mg of Ti3C2Tx MXene in 200 mL of ultrapure water and ultrasonicating to obtain a mixed solution I;

[0055] Step 2, adding a certain mass of FeCl3·6H2O and NH4VO3 into the mixed solution I and stirring evenly to obtain a mixed solution II;

[0056] Step 3, filtering the mixed solution II, and vacuum drying it in a vacuum drying oven at 60° C. to obtain a solid powder I;

[0057] Step 4: Place the solid powder I in a tube furnace and heat it at 5°C min under a protective atmosphere (nitrogen in this example). -1 The temperature is raised to a certain temperature at a heating rate and then kept at that temperature for 2 hours to obtain solid powder II; the purpose of the protective atmosphere is to isolate oxygen and prevent the carbon in the material from being oxidized and lost.

[0058] Step 5, the solid powder II is washed with 0.2M HCl solution, followed by ultrasonic treatment (300W, 25kHz) at 25°C for 4 hours; the product is then washed with ethanol and ultrapure water several times until the solution pH>6.5, taken out and filtered, and vacuum dried at 60°C to finally obtain an iron / vanadium diatomic catalyst.

[0059] In some embodiments, the masses of FeCl3·6H2O and NH4VO3 are 0.166-1.66 g and 0.072-0.72 g, respectively, and the heating temperature is 500-900°C.

[0060] The invention also provides a method for treating bisphenol A in water, which comprises first adding the iron / vanadium diatomic catalyst and mixing them evenly, and then adding PMS.

[0061] In some embodiments, the pH of the water body is 3-11, and the water body temperature is 293-313K; the dosage of the composite material is 0.5-2.0 g / L.

[0062] The present invention also provides a method for deeply treating the effluent of photovoltaic wastewater, and the method for treating photovoltaic wastewater comprises: fixing the iron / vanadium diatomic catalyst in a filtering and treating device so that the photovoltaic wastewater mixed with potassium monosulfate passes through, that is, completing the photovoltaic wastewater treatment and discharging the treated water. In some embodiments, the iron / vanadium diatomic catalyst is placed in a columnar reactor (filtering and treating device), the top and bottom of the reactor are respectively fixed with PVDF membranes, potassium monosulfate is added to the photovoltaic wastewater, and after mixing, it enters the reactor from the top and the bottom is discharged. The PVDF membrane is used to fix the iron / vanadium diatomic catalyst so that the photovoltaic wastewater can pass through the catalyst evenly.

[0063] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0064] Unless otherwise specified, the raw materials and reagents involved in the embodiments of the present invention are all commercially available. Among them, Ti3C2TxMXene was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0065] Example 1

[0066] 1. Screening of diatomic catalysts

[0067] The adsorption energy and the amount of electron transfer between the carrier and the persulfate molecules are regarded as the main descriptors for evaluating the catalyst's ability to adsorb and activate PMS, and the M-MXene loaded with single-atom metals (V, Mn, Fe, Co, Cu, Ni, Zn) is screened in the first step; the M-MXene (V, Mn, Fe) with the highest adsorption energy or the amount of electron transfer between the carrier and the persulfate molecules is regarded as a potential diatomic pairing choice, and further a new diatomic pairing carrier M1-M2-MXene is obtained through two pairing methods; the M1-M2-MXene with the highest adsorption energy or the amount of electron transfer between the carrier and the persulfate molecules is regarded as a potential high-efficiency catalyst, and the efficient electron transfer between the diatoms is further analyzed by charge density difference and differential charge, and the highly active diatomic catalyst Fe-V-MXene is screened out.

[0068] 2. Synthesis of Fe-V-MXene

[0069] (1) 400 mg of Ti3C2Tx MXene was dispersed in 200 mL of ultrapure water and ultrasonicated to obtain a mixed solution I;

[0070] (2) Add 0.83 g of FeCl3·6H2O and 0.36 g of NH4VO3 to the mixed solution I and stir evenly to obtain a mixed solution II;

[0071] (3) filtering the mixed solution II, and then vacuum drying it in a vacuum drying oven at 60° C. to obtain a solid powder I;

[0072] (4) placing solid powder I in a tube furnace, heating the temperature to 600° C. at a heating rate of 5° C. / min under a nitrogen atmosphere, and then keeping the temperature for 2 h to obtain solid powder II;

[0073] (5) The solid powder II was washed with 0.2 M HCl solution, and then ultrasonically treated (300 W, 25 kHz) at 25 °C for 4 h. The product was then washed several times with ethanol and ultrapure water until the pH of the solution was >6.5. The product was taken out, filtered and vacuum dried at 60 °C to finally obtain an iron / vanadium diatomic catalyst.

[0074] Example 2

[0075] 1. Screening of diatomic catalysts is the same as in Example 1

[0076] 2. Synthesis of Fe-V-MXene

[0077] (1) 400 mg of Ti3C2Tx MXene was dispersed in 200 mL of ultrapure water and ultrasonicated to obtain a mixed solution I;

[0078] (2) Add 1.66 g of FeCl3·6H2O and 0.72 g of NH4VO3 to the mixed solution I and stir evenly to obtain a mixed solution II;

[0079] (3) filtering the mixed solution II, and then vacuum drying it in a vacuum drying oven at 60° C. to obtain a solid powder I;

[0080] (4) placing solid powder I in a tube furnace, heating the temperature to 600° C. at a heating rate of 5° C. / min under a nitrogen atmosphere, and then keeping the temperature for 2 h to obtain solid powder II;

[0081] (5) The solid powder II was washed with 0.2 M HCl solution, and then ultrasonically treated (300 W, 25 kHz) at 25 °C for 4 h. The product was then washed several times with ethanol and ultrapure water until the pH of the solution was >6.5. The product was taken out, filtered and vacuum dried at 60 °C to finally obtain an iron / vanadium diatomic catalyst.

[0082] Example 3

[0083] 1. Screening of diatomic catalysts is the same as in Example 1

[0084] 2. Synthesis of Fe-V-MXene

[0085] (1) 400 mg of Ti3C2Tx MXene was dispersed in 200 mL of ultrapure water and ultrasonicated to obtain a mixed solution I;

[0086] (2) Add 0.83 g of FeCl3·6H2O and 0.36 g of NH4VO3 to the mixed solution I and stir evenly to obtain a mixed solution II;

[0087] (3) filtering the mixed solution II, and then vacuum drying it in a vacuum drying oven at 60° C. to obtain a solid powder I;

[0088] (4) placing solid powder I in a tube furnace, heating the temperature to 800° C. at a heating rate of 5° C. / min under a nitrogen atmosphere, and then keeping the temperature for 2 h to obtain solid powder II;

[0089] (5) The solid powder II was washed with 0.2 M HCl solution, and then ultrasonically treated (300 W, 25 kHz) at 25 °C for 4 h. The product was then washed several times with ethanol and ultrapure water until the pH of the solution was >6.5. The product was taken out, filtered and vacuum dried at 60 °C to finally obtain an iron / vanadium diatomic catalyst.

[0090] Example 4

[0091] 1. Screening of diatomic catalysts is the same as in Example 1

[0092] 2. Synthesis of Fe-V-MXene

[0093] (1) 400 mg of Ti3C2Tx MXene was dispersed in 200 mL of ultrapure water and ultrasonicated to obtain a mixed solution I;

[0094] (2) Add 0.83 g of FeCl3·6H2O and 0.36 g of NH4VO3 to the mixed solution I and stir evenly to obtain a mixed solution II;

[0095] (3) filtering the mixed solution II, and then vacuum drying it in a vacuum drying oven at 60° C. to obtain a solid powder I;

[0096] (4) placing solid powder I in a tube furnace, heating the temperature to 600° C. at a heating rate of 5° C. / min under a nitrogen atmosphere, and then keeping the temperature for 2 h to obtain solid powder II;

[0097] (5) The solid powder II was washed with 0.2 M HCl solution, and then ultrasonically treated (300 W, 25 kHz) at 25 °C for 4 h. The product was then washed several times with ethanol and ultrapure water until the pH of the solution was >6.5. The product was taken out, filtered and vacuum dried at 60 °C to finally obtain an iron / vanadium diatomic catalyst.

[0098] Treatment of Bisphenol A (BPA) in Water

[0099] Determination of BPA: The concentration of BPA was determined by high performance liquid chromatography, with the following detection parameters: wavelength 278 nm, mobile phase methanol-deionized water (70:30, v / v), flow rate 1.0 mL min -1 All degradation experiments were carried out in a batch reactor using a 150 mL conical flask under magnetic stirring at 25 °C. First, 25 mg of catalyst (0.5 g·L -1 ) Add 50mL BPA (20mg·L -1 ) and 2 mM PMS, and then placed the conical flask on a constant temperature shaker at a speed of 170 rad·min -1 . The pH value of the initial solution was adjusted by H2SO4 and / or NaOH solution. Subsequently, the reaction solution was sampled at certain time intervals and filtered with a 0.45 μm membrane filter. Since PMS will continue to generate free radicals and continue oxidation to interfere with the measurement data, in some embodiments, Na2S2O3 solution (0.1 M) was also added to the solution as an inhibitor to avoid continued oxidation.

[0100] Example 5: Treatment of BPA in water

[0101] The pH of the initial solution was adjusted to 3 using H2SO4 solution. Samples were taken every 1 minute to measure the BPA concentration. The BPA concentration was 0 mg·L-1 after 5 minutes of measurement. The removal efficiency was calculated to be 100%.

[0102] Example 6: Treatment of BPA in water

[0103] The pH of the initial solution was adjusted to 5 using H2SO4 solution. Samples were taken every 1 minute to measure the BPA concentration. The BPA concentration was 0 mg·L-1 after 5 minutes of measurement. The removal efficiency was calculated to be 100%.

[0104] Example 7: Treatment of BPA in water

[0105] The pH of the initial solution was adjusted to 7 using H2SO4 and NaOH solutions. Samples were taken every 1 minute to measure the BPA concentration. The BPA concentration after 5 minutes was 0.27 mg·L-1. The removal efficiency was calculated to be 98.9%.

[0106] Example 8: Treatment of BPA in water

[0107] The pH of the initial solution was adjusted to 9 using NaOH solution. Samples were taken every 1 minute to measure the BPA concentration. The BPA concentration was 0 mg·L-1 after 5 minutes of measurement. The removal efficiency was calculated to be 100%.

[0108] Example 9: Treatment of BPA in water

[0109] The pH of the initial solution was adjusted to 11 using NaOH solution. Samples were taken every 1 minute to measure the BPA concentration. The BPA concentration after 5 minutes was 0.49 mg·L-1. The removal efficiency was calculated to be 97.6%.

[0110] Figure 6 Figure 2 is a graph showing the removal efficiency of bisphenol A by Fe-V-MXene activated with PMS in Examples 5 to 9. It can be seen from the figure that the pH of the initial solution has a relatively limited effect on the removal of BPA in the Fe-V-MXene / PMS system. Figure 6 As shown in Figure 2, Fe-V-MXene exhibits significant catalytic activity in a wide pH range (3.0-11.0). In the initial pH range of 3.0-9.0, the BPA removal efficiency remains above 98% after 5 minutes, and the corresponding reaction rate constant (k obs ) values ​​range from 0.98 to 1.25min -1 However, at a solution pH of 11, a slight inhibition of BPA degradation was observed, k obs Down to 0.82min -1 This inhibition is mainly attributed to the strong alkaline conditions of HSO5 -Converted to SO5 2- and the conversion of BPA molecules into BPA - (pKa = 9.6), thus hindering the catalytic process.

[0111] Example 10: Treatment of BPA in water

[0112] All degradation experiments were carried out in a batch reactor using a 150 mL conical flask at 25 °C under magnetic stirring. First, 25 mg of catalyst (0.5 g L -1 ) Add 50mL BPA (20mg·L -1 ) and 2 mM PMS, and then placed the conical flask on a constant temperature shaker at a speed of 170 rad·min -1 Subsequently, the reaction solution was sampled at certain time intervals and filtered with a 0.45 μm membrane filter. Na2S2O3 solution (0.1 M) was added to the solution to avoid continuous oxidation. The 5-min BPA concentration was determined to be 0.27 mg·L-1, and the removal efficiency was calculated to be 98.9%.

[0113] Example 11: Treatment of BPA in water

[0114] Same as Example 10, except that the catalyst dosage is 0.25 g·L -1 The BPA concentration was measured to be 2.11 mg·L-1 after 5 minutes, and the removal efficiency was calculated to be 89.5%.

[0115] Example 12: Treatment of BPA in water

[0116] Same as Example 10, except that the catalyst dosage is 1.0 g·L -1 The BPA concentration after 5 minutes was measured to be 0 mg·L-1, and the removal efficiency was calculated to be 100%.

[0117] Figure 7 The removal efficiency of BPA by Fe-V-MXene activated PMS in Examples 10-12, where C t is the concentration changing with time, C0 is the initial concentration; it can be seen from the figure that the catalyst dosage is increased from 0.25g·L -1 Increase to 1g·L -1 While keeping the PMS dosage unchanged, the removal efficiency was significantly improved, kobs from 0.45min -1 Improved to 1.39min -1 This improvement is attributed to the increase in active sites after the addition of the catalyst, which promotes the generation of more active species.

[0118] Example 13: Deep treatment of photovoltaic wastewater effluent

[0119] A continuous flow experiment was conducted using photovoltaic wastewater effluent. The specific water sample was taken from the effluent of the secondary sedimentation tank of the industrial wastewater treatment plant in the Zero Carbon Industrial Park, Mengsu Economic Development Zone, Ordos City. The continuous flow experiment was carried out in a column reactor with a diameter of 3 cm and a reaction temperature of 25°C. Figure 8 As shown, the catalyst is highly dispersed and then vacuum filtered onto a polyvinylidene fluoride (PVDF) membrane to assemble into a continuous flow treatment device, which is used to further deeply treat the effluent of photovoltaic wastewater. The continuous flow treatment device comprises a supporting substrate IV, a PVDF membrane III, Fe-V-MXene II, and a PVDF membrane I arranged in sequence from bottom to top.

[0120] Photovoltaic wastewater mainly contains organic matter (such as polyethylene glycol) and various inorganic ions (F - , Cl - etc.), which are difficult to biodegrade and difficult to handle in practice. Fig. 9 As shown in Figure 2, the water flow rate of the Fe-V-MXene / PVDF membrane is maintained at 80-100 L·m -2 ·h -1 After 8 hours of long-term testing, the actual effluent COD removal rate was >70%, and the TOC removal rate was >45%. This result shows the good long-term stability and practical application potential of Fe-V-MXene.

[0121] In the present invention, the composite material adsorbs and removes Cd 2+ The effective pH range is 4 to 7, which is close to the pH value of cadmium-contaminated water bodies, so the adsorbent can be used for the treatment of actual water bodies.

[0122] Example 14: Comparison with Similar Catalysts

[0123] Table 1: Parameters compared with similar catalysts

[0124]

[0125]

[0126] Note: The references in Table 1 are:

[0127] [1]

[0128] [2]X.Chen,F.O.Gudda,X.Hu,M.G.Waigi,Y.Gao,Degradation of bisphenol Ain an oxidation system constructed from Mo2C MXene and peroxymonosulfate,npjClean Water,5(2022)66.

[0129] [3]Y.Long,Z.Cao,W.Wu,W.Liu,P.Yang,X.Zhan,R.Chen,D.Liu,W.Huang,Rational modulation of Fe single-atom electronic structure in a Fe-N2B4configuration for preferential 1O2generation in Fenton-like reactions,AppliedCatalysis B-Environment and Energy,344(2024).

[0130] [4]Y.Liu,R.Luo,Y.Li,J.Qi,C.Wang,J.Li,X.Sun,L.Wang,Sandwich-likeCo3O4 / MXene composite with enhanced catalytic performance for Bisphenol Adegradation,Chemical EngineeringJournal,347(2018)731-740.

[0131] [5]P.Yang,Z.Cao,Y.Long,D.Liu,W.Huang,S.Zhan,M.Li,Regulating theLocalElectronic Structure of Copper Single Atoms with Unsaturated B,O-Coordination for Selective 1O2Generation,ACS Catalysis,13(2023)12414-12424.

[0132] [6]P.Yang,S.Li,L.Xiaofu,A.Xiaojing,D.Liu,W.Huang,Singlet oxygen-dominatedactivation of peroxymonosulfate by CuO / MXene nanocomposites forefficient decontamination ofcarbamazepine under high salinity conditions:Performance and singlet oxygen evolutionmechanism,Separation and PurificationTechnology,285(2022)120288.

[0133] [7]Q.Zhou,P.Hong,X.Shi,Y.Li,K.Yao,W.Zhang,C.Wang,J.He,K.Zhang,L.Kong,Efficient degradation of tetracycline by a novel nanoconfinement structureCu2O / Cu@MXenecomposite,Journal of Hazardous Materials,448(2023)130995.

[0134] [8]X.Cui,S.-S.Zhang,Y.Geng,J.Zhen,J.Zhan,C.Cao,S.-Q.Ni,Synergisticcatalysis byFe3O4-biochar / peroxymonosulfate system for the removal ofbisphenol a,Separation andPurification Technology,276(2021)119351.

[0135] [9]Z.Yang,Z.Wang,G.Liang,X.Zhang,X.Xie,Catalyst bridging-mediatedelectron transferfor nonradical degradation of bisphenol A via naturalmanganese ore-cornstalk biochar compositeactivated peroxymonosulfate,ChemicalEngineering Journal,426(2021)131777.

[0136]

[10] Z.Zhang,H.Ding,Y.Li,J.Yu,L.Ding,Y.Kong,J.Ma,Nitrogen-dopedbiocharencapsulated Fe / Mn nanoparticles as cost-effective catalysts forheterogeneous activation ofperoxymonosulfate towards the degradation ofbisphenol-A:Mechanism insight and performanceassessment,Separation andPurification Technology,283(2022)120136.

[0137]

[11] X.Wang,W.Li,L.Yang,G.Zhao,J.Zhang,Q.Zhao,Phytic acid-modulatedironphosphide / biochar catalyst activates persulfate for rapidsulfamethoxazole removal:Synergybetween iron phosphides and biochar,ChemicalEngineering Journal,472(2023)144897.

[0138]

[12] P. Zhang,

[0139]

[13] C. Wang, X. Wang, W. Wu, Y. Zong, Z. Zhang, Y. Li, S. Qin, F. Wang, Technology,323(2023)124302.

[0140] As can be seen from Table 1, the Fe-V-MXene prepared in this application has a strong performance in activating PMS. At the same time, it also proves the feasibility and superiority of the screening method of the invention. The density functional theory calculation screening method for diatomic catalysts described in the present invention shows an efficient screening principle. The iron / vanadium diatomic catalyst activated PMS based on MXene prepared by this method has a high and stable removal rate and efficiency for bisphenol A in the water pH range of 3-11. Compared with Fe3O4@MXene (0.039min -1 )、Mo2C MXene(0.023min -1 )、FeNx-B-2Mxene(0.25min -1 )、Cu-SA / B-MXene-4(0.23min -1) and other catalytic materials, Fe-V-MXene can completely remove 20 mg / L BPA within 6 minutes, and the maximum reaction rate constant can reach 0.98 min -1 . And it can show good anti-interference ability and long-term stability in difficult-to-degrade photovoltaic wastewater.

[0141] In summary, the adsorption energy and charge transfer of the present invention are used as descriptors to correspond to the adsorption and activation stages of PMS. The adsorption energy of the present invention is only used as a pre-screening. The actual evaluation also combines the charge transfer ability, and further analyzes the d-band center and state density of different diatomic catalysts. The catalyst material of the present invention has good stability. After five regeneration tests, the removal rate of BPA by the catalyst material is still above 90%. In addition, the Fe-V-MXene / PMS / PVDF system developed based on Fe-V-MXene catalyst shows good application potential in the deep treatment of photovoltaic wastewater, and the TOC treatment efficiency after 8h stable operation is still above 45%. On the whole, the Fe-V-MXene prepared in this application does not require such cumbersome steps, and the reaction range is also very broad, showing good application prospects.

[0142] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for screening diatomic catalysts based on density functional theory calculations, characterized in that: The following steps are involved: Step S1, using adsorption energy and electron transfer amount as descriptors for evaluating the ability of the catalyst to adsorb and activate PMS, the M-MXene loaded with single-atom metals is sorted from high to low according to the adsorption energy, and the first n M-MXenes are obtained, thereby screening n types of metals M; Step S2, pairing the n metals M in pairs to obtain a diatomic pairing carrier M1-M2-MXene group; Step S3, performing differential charge calculation on the M1-M2-MXene group, and selecting the M1-M2-MXene with the highest electron transfer amount as a diatomic catalyst.

2. The method for screening diatomic catalysts based on density functional theory calculations according to claim 1, characterized in that: The single-atom metals include at least four of iron, copper, cobalt, manganese, vanadium, nickel, and zinc.

3. The method for screening diatomic catalysts based on density functional theory calculations according to claim 1, characterized in that: The n is 3 or 4, and the M1-M2-MXene is an iron / vanadium diatomic catalyst.

4. A method for preparing an iron / vanadium diatomic catalyst, characterized in that: The method includes: Step 1: Ti3C2T x MXene is dispersed in ultrapure water to obtain mixed solution I; Step 2, adding FeCl3·6H2O and NH4VO3 into the mixed solution I and stirring evenly to obtain a mixed solution II; Step 3, filtering the mixed solution II and drying it to obtain solid powder I; Step 4, placing the solid powder I in a tube furnace and calcining at high temperature under a protective atmosphere to obtain a solid powder II; Step 5, washing the solid powder II with acid and water for several times until the pH of the solution is >6.5, filtering, and drying to obtain iron / vanadium diatomic catalyst powder.

5. The method for preparing the iron / vanadium diatomic catalyst according to claim 4, characterized in that: The molar ratio of FeCl3·6H2O to NH4VO3 is 1:(1-2).

6. The method for preparing the iron / vanadium diatomic catalyst according to claim 4, characterized in that: In step 4, the high temperature calcination temperature is 500℃~900℃, and the heating rate is 3-10℃·min -1 .

7. An iron / vanadium diatomic catalyst, characterized in that It is formed by loading iron and vanadium in Ti3C2Tx MXene, wherein the molar ratio of iron to vanadium is 1:(1-2), and the molar ratio of Fe to Ti3C2Tx MXene is (0.25-1):

1.

8. Use of the iron / vanadium diatomic catalyst as claimed in claim 7, characterized in that: Used to treat bisphenol A in water bodies or for treating photovoltaic wastewater.

9. The use of the iron / vanadium diatomic catalyst as claimed in claim 8, characterized in that: The method for treating bisphenol A in water comprises: adding the iron / vanadium diatomic catalyst to the water to be treated and mixing evenly, then adding potassium peroxymonosulfate, adjusting the pH of the water to 3-11 and the water temperature to 293-313K; wherein the dosage of the iron / vanadium diatomic catalyst is 0.5-2.0 g / L.

10. The use of the iron / vanadium diatomic catalyst according to claim 8, characterized in that: The method for treating photovoltaic wastewater comprises: fixing the iron / vanadium diatomic catalyst in a filtering treatment device, allowing photovoltaic wastewater mixed with potassium monopersulfate to pass through, and discharging treated water.

Citation Information

Cited By

  • Method for precisely designing and efficiently screening diatomic catalyst based on MXenes and applying diatomic catalyst to CO2RR

    CN121687225A

  • A method for precise design and efficient screening of diatomic catalysts based on MXenes and their application in CO2RR

    CN121687225B